Corrections to "A checklist of the butterflies of Melanesia, Micronesia, Polynesia and some adjacent areas" published in Zootaxa, 1178 (2006) - Tennent, W. John (Zootaxa, 2006)
In a recent Pacific butterfly checklist (Tennent, 2006) the author commented on the dates of publication of butterfly names published by Arthur Gardiner Butler in the Proceedings of the Zoological Society of London for 1875, pointing out that both 1875 and 1876 had been used by authors over the years in referring to publication dates in Butler (1876a: given in the Pacific checklist as 1875a). Although it was acknowledged that 1876 might have been the correct date of publication, the more frequently used date of 1875 was adopted in the checklist in the interests of conformity, accompanied by an explanatory footnote (Tennent, 2006: 156 [note 38]). It transpires that this was erroneous.